EVALUATION OF SHIELDING BARRIER OF A COMPUTED TOMOGRAPHY UNIT - Muhammad, B. G.; Sani, U.; Usman, A. R.; Joseph, D. S. (FUDMA JOURNAL OF SCIENCES, 2020)
Recently, concerns have been expressed on the radiological standards of Computed Tomography (CT) units in terms of radiation protection. This study was carried out in the CT scan unit of General Amadi Rimi Specialist Hospital (GARSH), Katsina, Nigeria. The study aimed to evaluate the radiation shielding barrier of a Computed Tomography unit of GARSH, Katsina, Nigeria. The main objective of this study is to determine the shielding barrier thickness required to attenuate the unshielded radiation. Calculations of the shielding barrier thickness were carried out using XRAYBARR software. The total workload for the CT modality was found to be 48.32 mA-min per week for an average of 32 patient per week. The shielding barrier thickness required in attenuating the unshielded radiation dose for wall 1, 2, 3, 4, control area, floor and ceiling was 155.1, 146.8, 112.5, 98.10, 98.10, 193.0 and 128.0 mm thickness concrete, respectively. The already constructed shielding barrier thickness was found to be 244mm thickness concrete. Ratio of the calculated barrier thickness to the designed barrier thickness was less than 1. This showed that the constructed shielding barrier thickness was adequate and safe. The area monitoring of the strategic areas in the CT unit was carried out using calibrated radiation survey meter. The result revealed that, the background and leakage radiation doses were within the recommended dose limit. High radiation dose was recorded at the door of the CT scan room. It was recommended that the occupational workers should always use thyroid shield and light-lead glasses.